Recensiones - Achaerandio, Luis; S. J.,; Zuluaga de Villacorta, Carmenza (ECA: Estudios Centroamericanos, 1978)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 33, No. 353, 1978: 189.